Work climate and economic performance in sustainable companies - Anastasia-Cristiana Dumitru; Bucharest University of Economic Studies (Cactus)
This research aimed to investigate the relationship between work climate, sustainability practises and perceived economic performance in sustainable companies, focusing on the impact of Environmental, Social, and Governance (ESG) initiatives. The main objective is to assess how workplace climate influence economic performance and how sustainability practices contribute to employee satisfaction. The study uses a quantitative methodology based on a questionnaire consisting of 15 questions distributed to employees of sustainable companies. The collected data were statistically analysed using SPSS software, with correlation and linear regression tests to validate the hypotheses. Three main hypotheses were tested in the study: (H1) the positive relationship between a favourable work climate and economic performance, (H2) the contribution of sustainability practises to improving work climate, and (H3) the correlation between involvement in ESG initiatives and employee satisfaction. The results indicate a significant correlation between a positive work climate and perceived economic performance as well as a correlation between the implementation of ESG initiatives and employee satisfaction. This research contributes to the understanding of how sustainability practises can influence both employee satisfaction and overall business performance and provides guidance for improving organisational strategies in sustainable companies.